Feasibility of Screening Primary Aldosteronism by Aldosterone-to-Direct Renin Concentration Ratio Derived from Chemiluminescent Immunoassay Measurement: Diagnostic Accuracy and Cutoff Value. (2nd July 2019) - Li, Tianqi; Ma, Yeshuo; Zhang, Ying; Liu, Yue; Fu, Tingting; Zhang, Ri; Kang, Kai; Yang, Yingchao; Wang, Lixin; Jiang, Yinong; Lu, Yan
Abstract : Objectives . Aldosterone-to-plasma renin activity ratio (ARR) derived from traditional radioimmunoassay (RIA) is widely used to detect primary aldosteronism (PA). Recently, aldosterone-to-direct renin concentration ratio (ADRR), which is calculated by direct renin concentration (DRC) measured by chemiluminescent immunoassay (CLIA), is proposed to replace ARR as the screening test method for PA. The purpose of the present study was to estimate the diagnostic accuracy and cutoff value of ADRR as screening test for PA. Methods . 450 hypertensive patients with suspected PA referred to hypertension center of our department were enrolled and underwent screening and confirmatory tests of PA. Plasma renin activity (PRA), DRC, and plasma aldosterone concentration (PAC) were measured by both RIA and CLIA simultaneously during screening and confirmatory test. Results . 386 patients were diagnosed as primary hypertension (PH) and 64 patients as PA. Within-patient correlation between PRA and DRC (r=0.88, P<0.001) and correlation between PAC measured by RIA and CLIA were high (r=0.80, P<0.001). The optimal cutoff value of ADRR was 2.93 (ng/dL)/(mU/L), sensitivity 80.33%, and specificity 92.11%. The optimal cutoff value of ARR was 25.28 (ng/dL)/(ng/mL/h), sensitivity 76.92%, and specificity 93.38%. Conclusion . The optimal cutoff values of ADRR and ARR for screening PA are defined in this patient cohort with high sensitivity and specificity. Our results are of clinical importance for accelerating the extensive use of ADRR as a screening test for PA in daily practice.